Memory symposium: education and gender. - Villareal Montoya, Ana Lucía (2011)
The report includes the abstracts of the research program, who presented both a summary of each of the investigations, as your answers / comments to questionsgenerators put to them in order to gospecifying specific contributions from the research, they selected what to answer, as itraised as a guide.